HASTE diffusion-weighted 3-Tesla magnetic resonance imaging in the diagnosis of primary and relapsing cholesteatoma - Pizzini, Francesca B; Barbieri, Franco; Beltramello, Alberto; Alessandrini, Franco; Fiorino, Francesco (Otology & neurotology, 2010)
To evaluate the value of half-Fourier acquisition single-shot turbo-spin-echo diffusion-weighted magnetic resonance imaging (HASTE DW MRI) using a 3-Tesla (3T) unit in the diagnosis of primary and relapsing cholesteatoma. Retrospective observational investigation. Tertiary referral center. Seventeen patients suspected of having a primary cholesteatoma without clear clinical evidence of the lesion, and 13 patients who were candidates to a second-stage tympanoplasty to rule out a relapsing cholesteatoma or reconstruct the ossicular chain were investigated. All patients were scanned in a 3T scanner with a 4-channel head coil using T2 HASTE DW MRI technique sequences in axial and coronal planes covering the middle ear and mastoid regions. Images were considered positive for cholesteatoma in the presence of a hyperintense, patchy-like lesion in the petrous bone. Images showed a high signal intensity suggestive of primary cholesteatoma in 10 of 17 patients and of relapsing cholesteatoma in 7 of 13 patients. Of the 17 subjects, 15 with positive MRI findings were operated on, and the presence of cholesteatoma (ranging from 2 to 20 mm in size) was confirmed at surgery. Of the 13 subjects shown to be negative on HASTE DW MRI for cholesteatoma, 11 were operated on and were all confirmed to be cholesteatoma-free. Half-Fourier acquisition single-shot turbo-spin-echo diffusion-weighted magnetic resonance imaging technique, using a 3T unit, may be a diagnostic tool for a rapid and highly reliable discrimination between cholesteatomatous and noncholesteatomatous tissue in the middle ear, with 100% of positive and negative predictive values.